Edukasi Literasi Digital : Pendampingan Transformasi Digital bagi Generasi Muda di Desa Nepo Kabupaten Polewali Mandar - Ruslan, Ruslan; Ilham S, Muhammad; M, Irmawati; Fandini, Intan; Umar, Umar (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service activity aims to increase the understanding of young people in Nepo village regarding digital literacy and digital transformation assistance. The method of implementing this service uses socialization and training with a participatory approach. The evaluation instrument for this activity uses a questionnaire and is analyzed descriptively. The results of this service show that there has been a significant increase in participants' understanding of the concepts of digital literacy, digital transformation and social media. Digital literacy understanding increased from 50% to 79%, while benefits of digital literacy understanding rose from 50% to 87%. Participants also showed an increase in understanding the era of digital transformation (from 38% to 79%) and the impact of social media (from 43% to 93%). They also understand ethics and cyber security better, with significant improvements. The digital literacy education program in Nepo village has successfully achieved its goals, empowering the younger generation in digital literacy, digital transformation and social media ethics.